Tolerância de plantas de pinhão manso ao déficit hídrico em resposta a doses de brassinosteroides - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
This study aimed to identify the effect of brassinosteroids on the morphophysiological and biochemical caracteristics of Jatropha curcas L in response to water deficit. The study was conducted in a greenhouse at the State University of Goias, Ipameri Campus, using a completely randomized design ins a 5x2 factorial arrangement (plants submitted to five concentrations of brassinosteroids: 0 mg L-1 ; 2 mg L-1 ; 4 mg L-1 , 8 mg L -1 and 16 mg L-1 with two daily water supply levels: 50% and 100 evapotranspiration), with two leafs applications of the hormone and six replicates. Jatropha curcas seeds were sown in eight liters pots containing a mixture of soil, sand and bovine manure in the ratio of 3: 1: 0.5, respectively, permforming thinning at 10 days after the emergence (DAE), leaving one plant per pot as experimental unit. After analysis of the composition of the mixture, fertilization was carried ou at seven days after germination according to agronomic recommendations for the crop. The seedlings were irrigated daily with water volume corresponding to daily evapotranspiration, two leafs applications of the hormone with treatments dosages of 10 mL and 20 mL of solution at 30 and 60 DAE, using how to control distilled water. The treatment with water deficit was imposed at 70 DAE, subjecting half of the plants to water stress and the other half irrigated daily. At 100 DAE the morphophysiological and biochemical analyzes were performed. Data were evaluated by the Newman-Keuls test at the 5% probability level and regression analysis. The brassinosteroids minimized the damages of the water deficit and activated mechanisms of tolerance of plants of Jatropha curcas to the drought. Brassinosteroids potentiated the vegetative growth, biomass production, photosynthesis and biochemical activities of Jatropha curcas plants whitout water restriction. To increase vegetative growth, activation of the antioxidant mechanisms is recommended dose of 8 mg L-1 in plants irrigated with adequate water supply and 9 mg L-1 in plants under water deficit.
Keywords: Jatropha curcas L.; Biocombustível; Hormônio; Seca; Jatropha curcas L.; Biofuel; Hormone; Drought; CIENCIAS AGRARIAS